A new subspecies in the Turdus nudigenis complex (Aves: Turdidae) from the Cauca River valley of Colombia - Avendaño, Jorge Enrique; Cuervo, Andrés M.; Montoya, Paola; Pulgarín-R, Paulo C.; Stiles, F. Gary (Zootaxa, 2021)
The taxonomy of the T. nudigenis complex has historically been challenging due to the uniformity in plumage among taxa, poorly known vocal variation, and allopatric distributions. Recent phylogenetic analyses have contributed to understanding relationships within the genus; however, much remains to be learned about the extent of phenotypic and genetic differentiation within taxa and its implications in species limits. Here, we analyze the taxonomic status of an enigmatic member of the T. nudigenis complex restricted to the Cauca River valley of Colombia. Our phylogenetic analyses suggest that the Cauca valley population is genetically distinctive from other members of the complex, although its sister relationships with respect to T. grayi and T. nudigenis could not be fully resolved due to paraphyly in the group. Based on similarity of plumage, calls, and biogeographic proximity we tentatively treat this taxon as a new subspecies of T. grayi. Populations from the northern Caribbean T. grayi casius/incomptus and the new taxon inhabit similar environmental conditions, being apparently isolated by the humid Nechí lowlands. A formal analysis of vocalizations coupled with a more robust genomic dataset are needed to resolve the systematic affinities and taxonomic status of several members of the T. nudigenis complex.